The Use of Color Term in Branding, a Multimodality Case - Armaeni, Ni Kadek; Rajeg, I Made (e-Journal of Linguistics, 2021)
Branding is the activity that involving pictures, shapes and colors reflecting the excellence of a product. In every brand colors play important role to make a brand stands out. The color was chosen in order to represent certain meaning and called as color term. the purpose of this article is to find out the color chart that is used in order to determine the meaning of each colors as well as the colors represent in the branding. The Badung Regency Tourism Branding is one of branding that play with color terms. This brand was analysed by applying the psychological aspects of color (Birren,2013) compare with the chart proposed by the Tourism Minister of Republic of Indonesia and the multimodality definition proposed by Kress and Van Leeuwen (2001). The analysis showed that the brand applying more than one semiotic modes and each modes shows certain meaning.